2022
DOI: 10.1007/s11695-022-06233-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete Telehealth for Multidisciplinary Preoperative Workup Does Not Delay Time to Metabolic and Bariatric Surgery: a Pilot Study

Abstract: Purpose The COVID-19 pandemic accelerated implementation of telehealth throughout the US healthcare system. At our institution, we converted a fully integrated multidisciplinary bariatric clinic from face-to-face visits to entirely telehealth video/telephone visits. We hypothesized telehealth would increase the number of provider/patient encounters and therefore delay time to surgery. Methods This is a retrospective review of consecutive patients who underwent total tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Three patients (3.7%) in our study population switched to TC during the preoperative bariatric assessment and were operated when surgical rooms were reopened for nonemergency care, and all 3 are still in active follow-up. Mills et al recently reported completely virtualized multidisciplinary preoperative management during the pandemic without negative impact on preoperative workup in comparison with conventional management [34]. Several observational studies [17] have shown that TM integrated into preoperative bariatric programs improved overall patient satisfaction, connection with the multidisciplinary team, and perceptions regarding their knowledge of nutrition a healthier lifestyle.…”
Section: Questionsmentioning
confidence: 99%
“…Three patients (3.7%) in our study population switched to TC during the preoperative bariatric assessment and were operated when surgical rooms were reopened for nonemergency care, and all 3 are still in active follow-up. Mills et al recently reported completely virtualized multidisciplinary preoperative management during the pandemic without negative impact on preoperative workup in comparison with conventional management [34]. Several observational studies [17] have shown that TM integrated into preoperative bariatric programs improved overall patient satisfaction, connection with the multidisciplinary team, and perceptions regarding their knowledge of nutrition a healthier lifestyle.…”
Section: Questionsmentioning
confidence: 99%
“…This was in agreement with a recent study by Mills et al which reported a significant reduction in time and the number of visits from the initial appointment to bariatric surgery when patients received telehealth‐based versus in‐person care. Mills et al, however, did not assess no‐show rates or achieved any weight loss 7 . Every effort was made that both groups in the present study were scheduled to have the same appointment frequency to reduce any effect on program duration.…”
Section: Discussionmentioning
confidence: 87%
“…Mills et al, however, did not assess no-show rates or achieved any weight loss. 7 Every effort was made that both groups in the present study were scheduled to have the same appointment frequency to reduce any effect on program duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations